Bentuk Romantisme Russell Noyes dalam Novel”Maa Laa Nabuuhu Bih” Karya Sandra Siraj - Zarnubi, Muhammad; Surur, Misbahus (Faculty of Humanities, Diponegoro University, 2025)
Romanticism in social life has become a human instinct that is impossible to eliminate. The various expressions that humans express make life colorful. Just like the romanticism shown in the novel “Maa Laa Nabuuhu Bih” by Sandra Siraj makes the reader carried away with the story of the complexity of romanticism between the characters in it. This research aims to explain the forms of Russel Noyes' romanticism in the novel “Maa Laa Nabuuhu Bih” by Sandra Siraj. The method used was descriptive–qualitative. The primary data source was the novel “Maa Laa Nabuuhu Bih, ” by Sandra Siraj published by Daar Dawen in 2018, totaling 174 pages. Secondary data sources come from studies relevant to the discussion of this research. The data collection technique used reading and note-taking methods. The data were then analyzed by detecting, understanding, and revealing messages from several novel excerpts. The results of this study found 14 forms of Russel Noyes' romanticism: two return to nature, three melancholia, two sentimentalism, three exoticism, two primitivism, and two individualism. Based on these research results, it can be concluded that melancholy and sentimentalism often occur in social life. Melancholy is caused by longing and sentimentalism is a form of overflow of feelings to convince a partner. Similar to the stories and events described in the novel “Maa Laa Nabuuhu Bih’ by Sandra Siraj. The researcher hopes that this research will not only be useful for the academic world but also add insight into social life